Coherent transition radiation from short electron bunches - Thongbai C.S. (2014)
Coherent transition radiation can be produced when short electron bunches traverse a vacuum-metal interface. The radiation is of great interest as a potential high intensity THz or far-infrared radiation source and for femtosecond electron bunch length measurements. This paper presents experimental and theoretical investigation on the generation and characterization of high intensity coherent transition radiation from short electron bunches. © 2007 Elsevier B.V. All rights reserved.